The relationship between general self‐efficacy and nursing practice competence for second‐year nurses: Empirical quantitative research - Ryozo Tomita (Wiley, 2024)
Abstract Aim To examine the relationship between general self‐efficacy and nursing practice competence for nurses in the second year of employment. Design A cross‐sectional design was used. Data Sources The study included 596 nurses in their second year of employment at 75 medical facilities across Japan and used an online questionnaire survey for data collection. Results The covariance structure analysis showed the path from general self‐efficacy (latent variable) to nursing practice competence. Positive correlations were found between all factors on both scales. Multiple regression analysis results showed that the general self‐efficacy factors of 'positivity in behavior' and 'confidence in social competence' affect nursing practice competence. Conclusion This study emphasizes the importance of enhancing the general self‐efficacy of second‐year nurses to improve their nursing practice competence. To achieve this, it suggests developing strategies from the perspective of the factors that comprise general self‐efficacy. Implications for the Profession and Patient Care The findings suggest that improving general self‐efficacy can enhance nursing practice competence, which could inform the development of interventions to support nurses in improving their competence. The study provides basic data for improving nurses' practice competence. Impact This study is the first to establish a relationship between general self‐efficacy and nursing practice competence among second‐year nurses. It demonstrates the significance of general self‐efficacy in enhancing nursing practice competence, particularly for second‐year nurses worldwide who may be struggling with their nursing practice competence and considering leaving the profession. The findings offer practical implications for stakeholders involved in nursing education and training programs, with potential applications in professional development. Reporting Method This manuscript adheres to the STROBE guidelines for the reporting of cross‐sectional studies. Patient or Public Contribution There was no patient or public contribution.